An exploration into nephrology nurses' lived experiences of caring for dying patients with end stage kidney disease following withdrawal of dialysis - Bidii, Dempto Boniface (Division of Nursing and Midwifery, 2020)
The aim of this study sets out to better understand nephrology nurses’ lived experiences of dying and deaths of patients with ESKD following withdrawal of dialysis. A qualitative research design using an interpretative phenomenological approach was used to explore the experiences of a purposive heterogeneous sample of eight nephrology nurses who were working in private dialysis units. Information was gathered by phenomenological conversations and feed-back sessions. Colaizzi’s phenomenological method was employed to formulate four main themes: 1. Emotional trauma 2. Detachment 3. Loss of altruistic values in nursing 4. being-with-death For the participants in this study, emotional trauma was the most significant. The participants experienced a sense of powerlessness which caused emotions of hopelessness and anger and subsequently a sense of premature mourning and detachment. This state of hopelessness proved to be an obstacle in patient care, resulting in the altruistic values of nursing to be no longer applied. The participants’ ontological confrontation of being-with-death was evident, as they came to terms with the reality of their own death. Recommendations are offered to address the educational aspects of death and dying for nephrology nurses. This study endorses the need for further research into patients with ESKD ‘end-of-life’ which can influence how healthcare professionals should treat these patients during this phase.